Collaboration Patterns and Product Innovation in the Basque Country. Does a Firm’s Nationality Matter? - Henar Alcalde Heras (Journal of Entrepreneurship, Management and Innovation)

(untitled)
More and more, the ability to innovate can be considered as an explanatory factor in determining the long-term potential of firms to be competitive. Therefore, it is of increasing importance to understand the critical success factors behind notably radical product innovations. The present paper explores the yields and results in terms of a series of competitiveness indicators that domestic and foreign firms in the Basque Country obtain from technological collaboration practices. In particular, the study seeks to assess differences in the way these two groups of firms organize their technological partnerships (in terms of the geographical spread of partners with whom they cooperate and the purposes for which they deploy collaboration: for commercial or science/knowledge generation), and the comparative differences that stem from their respective practices. The study uses firm level data from the Euskadi Innovation Survey 2011, for firms located in the Basque Country. The paper finds that (a) technological collaborations comprising different types of partners have the greatest positive impact on innovation novelty, and (b) when looking at the firm’s nationality, collaboration strategies developed by foreign firms have a higher impact on achieving novel innovation. We posit that the higher degree of product innovation we observe among foreign firms – as opposed to domestic firms in the Basque Country – relies on their ability to benefit from both inter-regional partnerships and commercial-based networks for the sake of innovation purposes.